Repurposing of Pirfenidone (Anti-Pulmonary Fibrosis Drug) for Treatment of Rheumatoid Arthritis - Gan, Donghao; Cheng, Wenxiang; Ke, Liqing; Sun, Antonia RuJia; Jia, Qingyun; Chen, Jianhai; Lin, Jietao; Li, Jian; Xu, Zhanwang; Zhang, Peng (Frontiers in Pharmacology, 2021)
Clinical studies have shown that pirfenidone (PFD) effectively relieves joint pain in rheumatoid arthritis (RA) patients. However, the detailed mechanisms underlying the anti-RA effects of PFD have not been investigated. This study was undertaken to investigate the repurposing of PFD for the treatment of RA, and explore its anti-rheumatic mechanisms. A collagen-induced arthritis (CIA) rat model was used to observe joint pathological changes following PFD treatment. Based on bioinformatics to predict the mechanism of PFD anti-RA, using EA. hy926 and TNF-α-induced MH7A cells to establish in vitro model to explore its biological mechanism from the perspectives of synovial inflammation and angiogenesis. PFD significantly relieved pathological changes, including joint swelling, synovial hyperplasia, inflammatory cell infiltration and joint destruction. PFD was also associated with reduced expression of MMP-3 and VEGF in articular chondrocytes and synovial cells of CIA rats (p < 0.05). Using bioinformatic methods, we predicted that PFD inhibits cell inflammation and migration by interfering with the JAK2/STAT3 and Akt pathways. These results were verified using in vitro models. In particular, PFD effectively reduced the expression of pro-inflammatory, chondrogenic, and angiogenic cytokines, such as IL-1β, IL-6, IL-8, MMP-1/3/2/9 and VEGF (p < 0.05), in TNF-α-induced MH7A cells. In addition, PFD significantly reduced the production of MMP-2/9 and VEGF in EA. hy926 cells, thereby weakening migration and inhibiting angiogenesis (p < 0.05). These findings suggest that PFD may alleviate the pathological process in CIA rats, by inhibiting inflammation and angiogenesis through multiple pathways, and serve as a potential therapeutic drug for RA.